Effect of Ignition Point Location on Temperature Profile and Syngas Composition in Downdraft Gasification of Coconut Shell and Wood Sawdust - Purwinda Iriani; Tina Mulya Gantina; Yanti Suprianti (The University of Lampung, 2026)
The utilization of biomass waste as an energy source, such as for hydrogen and methane gas production, can be achieved through the gasification process. This study aims to analyze the performance of biomass gasification using coconut shells and wood sawdust for syngas production, by comparing the effects of different ignition point positions on process effectiveness. The gasification process was carried out using a down-draft type gasifier reactor. Two main variables were examined: the type of biomass (coconut shell and wood sawdust) and the ignition point location (upper and middle positions). The measured parameters included temperature profiles and syngas composition (H₂ and CH₄). The results showed significant differences based on the ignition point position. The upper ignition point only reached relatively low temperatures (72–262 °C) within six minutes, whereas the middle ignition point achieved a much higher operational temperature (825 °C) after 10 min of ignition. Syngas analysis revealed that wood sawdust produced a higher hydrogen content (4.46%) compared to coconut shell (1.79%), while coconut shell produced a higher methane content (3.4%) than wood sawdust (1.17%). These findings indicate that ignition location plays a critical role in controlling the thermal zone development and gasification efficiency. Optimizing ignition position can significantly improve syngas quality and reactor performance in downdraft gasification systems.